Ampliação de escala experimental da produção biotecnológica de xilitol a partir do hidrolisado do pedúnculo do caju - Medeiros, Lorena Lucena de (2015)
Due to the amount of waste generated by industries and commitments to the environment, there has been a growing interest in the use of alternative energy sources for the generation of bio-products with added value, such as ethanol and xylitol. In this context, cashew peduncle has been considered a promising alternative to meet this demand in a more sustainable manner. Thus, the aim of this study was to assess the expansion of the experimental scale of biotechnological xylitol production using liquor from the acid treatment of cashew peduncle bagasse as substrate and Candida guilliermondii CCT 3544 yeast as fermentation agent. Cashew peduncle bagasse was washed, dried at 55°C, ground, sieved (48 mesh), characterized and submitted to acid hydrolysis. Then, a 23 + 3 factorial experimental design with central points was performed in order to verify the effect of variables temperature, bagasse / dilute acid ratio and acid concentration on the release of pentose and hexose from hydrolyzed liquors. After hydrolysis, the liquor was submitted to concentration process and the fermentation medium was prepared in 400 ml Erlenmeyer flasks in Bioreactor (1600 ml), stirred at 200 rpm, 28°C from 0 to 120 h using C. guilliermondii CCT 3544 yeast. The characterization of the lignocellulosic composition revealed the presence of 21.45 ± 0.31% cellulose, 10.96 ± 0.31% hemicellulose and 35.39 ± 0.97% lignin, respectively. It was found that the liquor from the acid treatment should operate under temperature conditions at level 1 (160 ° C) and acid concentration, bagasse / dilute acid ratio at level -1 (1%, 1: 6). The overall analysis of results led to the conclusion that C. guilliermondii CCT-3544 was able to grow in medium with hydrolyzate, and its maximum concentration of cell growth was 3.5 g L-1 in both cases. However, the fermented concentrate obtained maximum production at 48 h of fermentation, but the fermented hydrolyzate in bioreactor produced ethanol and xylitol, with maximum xylitol production at 6 h and maximum ethanol production at 48 h of fermentation.